The Cambridge Companion to Literature and the Posthuman / Ed. - Rossini, Manuela; Clarke, Bruce (Cambridge : Cambridge University Press, 2017)
"The Cambridge Companion to Literature and the Posthuman is the first work of its kind to gather diverse critical treatments of the posthuman and posthumanism together in a single volume. Fifteen scholars from six different countries address the historical and aesthetic dimensions of posthuman figures alongside posthumanism as a new paradigm in the critical humanities. The three parts and their chapters trace the history of the posthuman in literature and other media, including film and video games; and identifies major political, philosophical, and techno-scientific issues raised in the literary and cinematic narratives of the posthuman and posthumanist discourses"--
Machine generated contents note: Preface: literature, posthumanism, and the posthuman Bruce Clarke and Manuela Rossini; Part I. Literary Periods: 1. Medieval Karl Tobias Steel; 2. Early modern Kevin LaGrandeur; 3. Romantic Ron Broglio; 4. Modern Jeff Wallace; 5. Postmodern Stefan Herbrechter; Part II. Posthuman Literary Modes: 6. Science fiction Lisa Yaszek and Jason W. Ellis; 7. Autobiography Kari Weil; 8. Comics and graphic novels Lisa Diedrich; 9. Film Anneke Smelik; 10. E-literature Ivan Callus and Mario Aquilina; Part III. Posthuman Themes: 11. The nonhuman Bruce Clarke; 12. Bodies Manuela Rossini; 13. Objects Ridvan Askin; 14. Technologies R. L. Rutsky; 15. Futures Claire Colebrook.
Keywords: Literature and technology; Humanism in literature; Mass media and technology; Human beings in literature